2020
DOI: 10.1101/2020.06.23.156653
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular signaling pathways underlying schizophrenia

Abstract: The molecular pathophysiological mechanisms underlying schizophrenia have remained unknown, and no treatment exists for primary prevention. Studies using stem cell-derived neurons have investigated differentially expressed genes (DEGs) and GO and KEGG pathways between patients and controls, but not analyzed data-driven causal molecular pathways involved. We used Ingenuity Pathway Analysis (IPA) to analyze canonical and causal pathways in two different datasets, including patients from Finland and USA. The most… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…In conclusion, our results showed that signaling pathways related to inflammation, synaptic functions, and especially, collagen and glycoprotein 6 pathways contributing to ECM are crucial in the etiology of SCZ. Abnormalities in ECM have been among the strongest findings in iPSCderived neurons in 3 other datasets 26,50 , which highlights its importance in the pathophysiological process. Finally, our results emphasize the importance of analyzing gene expression results separately for males and females.…”
Section: Discussionmentioning
confidence: 93%
“…In conclusion, our results showed that signaling pathways related to inflammation, synaptic functions, and especially, collagen and glycoprotein 6 pathways contributing to ECM are crucial in the etiology of SCZ. Abnormalities in ECM have been among the strongest findings in iPSCderived neurons in 3 other datasets 26,50 , which highlights its importance in the pathophysiological process. Finally, our results emphasize the importance of analyzing gene expression results separately for males and females.…”
Section: Discussionmentioning
confidence: 93%